Early school entrance and middle-run academic performance in Mexico: evidence for 15-year-old students from the PISA test - Aguayo Téllez, Ernesto; Martínez Rodríguez, Flor E. (SpringerOpen, 2020)
Using an unanticipated policy reform in Mexico that shifted 4 months the cutof date for elementary school eligibility in 2006 and information on academic performance of 15-year-old students from the Programme for International Student Assessment (PISA) 2018 survey, who entered frst grade in 2006, this paper estimates the efects of starting frst grade without having reached 6 years of age on middle-run academic performance. We found that entering school at a younger age increases the probability of having repeated at least one academic year by 7 percentage points and reduces academic performance (measured throughout PISA’s score points) between 6 and 10 score points in mathematics, reading and science (a Cohen’s d efect size between 0.06 and 0.10). We did not fnd evidence to claim that the efect of early entrance on academic performance is diferent for girls and boys or for urban and rural locations.